Karakteristik vegetasi penyusun habitat Lebah Madu Hutan (Apis dorsata. F) di hutan masyarakat Sungai Indragiri Riau - Michael Daru Enggar W; Avry Pribadi (Pelantar Press, 2018)
Habitat of Asian giant honeybee (Apis dorsata) and the forest that surround it play an important role for the development of bees. For local, honey gathered from the bees has important role in enhancing people`s live hood. However, studies examine the interaction between the bees and its vegetation is limited. The objection of this study were to (1) determine the number of the sialang trees and (2) to eamine structure of vegetation along the Indragiri river, Riau. The data were collected using the observation method by establishing many observation plots. The data were processed and analyze using quantative descriptive. The results showed that the structure of forests along the Indragiri river are consisted of several types of sialang trees, namely jelemu, arau, and stone wood. The diversity of plants is considerably high, such as Melastoma malabatrichum, rubber, ferns, acacia, and rattan at the seedling level and Macaranga sp, durio sp, rubber and meranti at the weaning level. The vegetation is considered still in good condition for bees` hive. Forest vegetation is dominated by the types of meranti, rubber, and the araceae family which can be used for either habitat or bee forage for bees.